Preparation and characterization of superior hydrophilic PVDF/DA membranes by the self-polymerization approach of dopamine - Li, Shaofeng; Zhang, Meilin; Sun, Jian; Sun, Jianping; Wang, Ying (Frontiers in Chemistry, 2023)
Polyvinylidene fluoride (PVDF) membranes are favored for their excellent properties. However, the inherent strong hydrophobicity of PVDF membranes limits their development in the field of water treatment. The objective of this study was to improve the performance of PVDF membranes using the self-polymerization, strong adhesion properties, and biocompatible effects of dopamine (DA). The PVDF/DA membrane modification conditions were simulated and optimized using response surface methodology (RSM), and the experimental design was used to investigate three main parameters. The results showed that the DA solution concentration of 1.65 g/L, the coating time of 4.5 h, the post-treatment temperature of 25°C, the contact angle decreased from 69° to 33.9°, and the pure water flux on the PVDF/DA membrane was higher than that on the original membrane. The absolute value of the relative error between the actual and predicted values is only 3.36 %. In the MBR parallel comparison test, compared with the PVDF/DA membrane, the total amount of extracellular polymers (EPS) of the PVDF membrane increased by 1.46 times and the polysaccharide increased by 1.56 times, which further showed that the PVDF/DA modified membrane had the excellent anti-pollution ability. Through Alpha diversity analysis, the biodiversity detected on PVDF/DA membranes was higher than that of PVDF membranes, which further proved its good bio-adhesion ability. These findings could offer a reference for the hydrophilicity, antifouling, and stability of PVDF/DA membranes, which would establish the foundation for the comprehensive applications in MBR.